Galvinoxyl radicals: Synthesis of new derivatives, determination of low oxygen contents, and stability studies. Issue 18 (3rd May 2019) - Lampp, Lisa; Azarkh, Mykhailo; Drescher, Malte; Imming, Peter
Abstract: Two new derivatives of galvinoxyl (1 ), a perdeutered (2 ) and an adamantyl-analog (3 ) for potential applications as spin probes were synthesized. The synthesis with deuterated educts yielded2 with 98% D. It exhibited an 18-line EPR spectrum in octanol with narrow peak-to-peak linewidth. The EPR spectrum of3 was very similar to galvinoxyl, but with differences in the linewidth due to unresolved long-range couplings with adamantyl-protons. Compound2 showed a higher response to oxygen (4.8 μT/% O2 ) than1 (2.8 μT/% O2 ). The coupling pattern of2 allowed the determination of oxygen at low levels (0–6%) by a new type of analysis of the EPR pattern. The stability of the radicals strongly depended on the amount of hydrogalvinoxyl, a by-product of the galvinoxyl synthesis, and the solvent type. A molecular mechanism for the stabilization by hydrogalvinoxyl and the influence of solvent type is proposed. Graphical abstract: Image 1 Highlights: Two new galvinoxyl derivatives were synthesized and characterized. Different methods for the synthesis of perdeuterated galvinoxyl were evaluated. The perdeuterated galvinoxyl showed good oxygen sensitivity at low oxygen content. A mechanism of stabilization of galvinoxyl by hydrogalvinoxyl was found. The influence of the solvent on the radical stability was studied.